The Effect Of Giving Lavender Aroma Therapy On The Pain Of Labor In The First Stage In Mothers In Labor At The Santi Meliala Inpatient Clinic In Medan - Sari, Indah Dewi; Harahap, Novy Ramini; Wulan, Mayang; Suwardi, Suyanti; Selvia, Selvia (Universitas Prima Indonesia, 2025)
The difference in levels of mild, moderate, severe and very severe pain requires different treatments according to the level, severe pain can cause complications during labor. Around 70% to 80% of women who give birth go through pain. One of the non-pharmacological therapies to reduce labor pain is with lavender aromatherapy. Purpose; this study was to determine the effect of giving lavender aromatherapy on labor pain in the first stage of labor in mothers giving birth at the Santi Meliala Clinic in 2024. Method; This study is a type of pre-experimental research with the design used being a pre-test post-test one group using the intervention of giving lavender aromatherapy. The population in this study were all mothers giving birth in the first stage as many as 15 people. Sampling using a purposive sampling technique, namely 15 people. The data collection instrument used the NRS observation sheet, then the data was analyzed using univariate and bivariate analysis. Bivariate analysis used a paired sample t-test comparison test with a significance level of 0.05). Results; The study showed a decrease in pain intensity in the pre-test and post-test, namely in the post-test the majority experienced moderate pain as many as 9 respondents (60%) and severe as many as 6 respondents (40%). After the intervention, the majority experienced mild pain as many as 8 respondents (53.3%) and the minority experienced moderate pain as many as 7 respondents (46.7%). The results of the paired t-test obtained a p-value = 0.000 (<0.05) which means there is a difference in the average pre-test and post-test. Conclusion; in this study, there is an effect of giving lavender aromatherapy on labor pain in the first stage of labor in mothers giving birth at the Santi Meliala Clinic in 2024. It is hoped that the clinic will implement lavender aromatherapy in reducing labor pain.